Addressing infodemic for pandemic preparedness in the digital age: a focus on Middle Africa - Penka, Marthe Bogne; Tangang, Andrew; Alang Wung, Ernest; Tata Kelese, Mark; Okwen, Patrick (Frontiers in Public Health, 2024)
Background The 21st century has brought about a damaging information crisis, significantly challenging and undermining efforts to increase the uptake of scientific research evidence in both policy and practice. The World Health Organization (WHO) recognizes misinformation and disinformation as major drivers of pandemic spread and impact, dedicating a policy brief to pandemic preparedness on this issue. In this study, we examine the impact of mis/disinformation on the use of research evidence in public policy decision-making in West and Central Africa and reflect on how this can inform future pandemic preparedness. Objectives What factors affect the uptake of scientific evidence during disease outbreaks in Africa? Methods We used the JBI Scoping Review and Prevalence/Incidence Review methodologies to synthesize the best available evidence. A DELPHI survey was conducted in two stages: the first gathered experiences from policymakers, practitioners, and citizens in Cameroon, Nigeria, and Senegal regarding mis/disinformation and its impact. The second stage explored potential situations related to the issues identified in the first stage. Qualitative data analysis was conducted using MAXQDA. Results The research identified the origins (n = 5), transmission platforms (n = 15), cases (n = 4), mitigation strategies (n = 6), and impacts (n = 4) of infodemic on policy design, implementation, and uptake. Online platforms were identified as the main source of infodemic in 53.3% of cases, compared to 46.7% attributed to offline platforms. We conclude that the severity of COVID-19 as a global pandemic has highlighted the dangers of mis/disinformation, with a considerable number of studies from Middle Africa demonstrating a significant negative impact on the uptake of health policies and to an extend evidence informed policy making. It is also imperative to consider addressing evidence hesitancy in citizens through innovative and indigenous approaches like storytelling. Discussions Digital technologies, especially social media, play a key role in the propagation of infodemics. For future pandemic preparedness, stakeholders must consider using digital tools and platforms to prevent and mitigate pandemics. This study adds new evidence to the existing body of evidence, emphasizing the need to address infodemics within the context of future pandemic preparedness in Middle Africa.